Implikasi metode pembelajaran kooperatif: Make a match dalam meningkatkan hasil kognitif siswa pada pembelajaran Al-Qur’an Hadits kelas XI Program Keagamaan MAN 3 Kediri - Mustofa, Labib (Maliki Interdisciplinary Journal, 2024)
This research aims to explore the implications of using the Make a Match cooperative learning method in improving students' cognitive outcomes in learning Al-Quran Hadith in class XI of the Religious Program at MAN 3 Kediri. This cooperative learning method was chosen because of its potential to increase student engagement and promote active learning. The sample for this research was class XI students of the MAN 3 Kediri Religious Program. Data was collected through cognitive outcome tests before and after treatment. Data analysis was carried out using descriptive and inferential statistical methods. The research results show that the use of the Make a Match cooperative learning method has a significant positive impact on improving students' cognitive outcomes in learning Al-Quran Hadith. This shows that this cooperative approach can be effective in increasing students' cognitive understanding of religious material. This research contributes to the cooperative learning literature and also provides practical implications for educators and curriculum developers in designing more effective learning strategies to facilitate students' understanding of religious material. Apart from that, this research also strengthens the argument for the importance of using active and participatory learning methods in the context of religious education.